Curriculum Reformulation in the Integrated Islamic School Network of Pariaman City as a Foundation for Implementing the Seven Habits of Outstanding Indonesian Children - Saputra, Aldi; Ritonga, Mahyudin; Syakban, Ismail (Universitas Muhammadiyah Magelang, 2025)
Curriculum plays a strategic role in shaping students”™ competencies and character. Integrated Islamic Schools (Sekolah Islam Terpadu, SIT), as flexible educational institutions, have the potential to integrate Islamic values with national character education programs, including the Seven Habits of Outstanding Indonesian Children (T7K). This study aims to (1) analyze the curriculum structure of the Integrated Islamic School Network (JSIT) in Pariaman City in accommodating the principles of T7K, (2) identify factors contributing to the low level of T7K integration, and (3) formulate a curriculum model that remains consistent with Islamic identity. The study employed a qualitative approach using Design-Based Research (DBR), with data collected through observations, in-depth interviews, and document analysis. Data were analyzed using the Miles and Huberman interactive model. The findings indicate that the JSIT curriculum in Pariaman combines the national curriculum, Ismubaris, integrated curriculum, and diniyah programs. However, the implementation of T7K remains limited due to parents”™ insufficient understanding, weak coordination among human resources, limited facilities, and the lack of specialized teacher training. The proposed curriculum reformulation emphasizes strengthening the boarding school model, enhancing teachers”™ capacity through T7K-based training, and promoting active parental involvement through structured parenting programs. These findings highlight the importance of collaboration among schools, families, communities, and government institutions in developing a holistic Islamic curriculum that aligns with national policies while sustaining Islamic educational values.